2020
DOI: 10.3389/fpsyg.2020.548781
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging as an Important Factor in the Pursuit of Physics: Does It Also Matter for Female Participants of the German Physics Olympiad?

Abstract: This paper focuses on stereotype threat and its effects on sense of belonging in the German Physics Olympiad science competition. Participants completed questionnaires about sense of belonging, stereotype endorsement, interest, and self-concept in physics, as well as about value and success expectations of studying physics in college. Female participants who endorsed negative stereotypes about female talent for physics felt less sense of belonging to physics. This effect did not manifest for male participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 89 publications
(119 reference statements)
0
9
0
1
Order By: Relevance
“…Research has pointed to a problem of the low presence of women in undergraduate Physics courses 6 which is the reason why their motivation to learn Physics in primary and secondary school should be considered. Some of the reasons are the decline in females’ interest in Physics 39 which can be influenced by situations or environments which could promote negative stereotypes or females’ non-identification with Physics. In order to determine the contribution of different learning environments on females’ motivation to learn Physics, in present study examined the impact of real and virtual experiments, as the two most common new approaches in teaching Physics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has pointed to a problem of the low presence of women in undergraduate Physics courses 6 which is the reason why their motivation to learn Physics in primary and secondary school should be considered. Some of the reasons are the decline in females’ interest in Physics 39 which can be influenced by situations or environments which could promote negative stereotypes or females’ non-identification with Physics. In order to determine the contribution of different learning environments on females’ motivation to learn Physics, in present study examined the impact of real and virtual experiments, as the two most common new approaches in teaching Physics.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption is that there is a deep belief among girls that Physics is not for them. Women and girls in Science are faced with negative stereotypes about them, which negatively impact their belonging to the group 39 . Because Physics identities are directly correlated with self-confidence 6 , it is necessary to apply an inclusive learning environment to prevent discrimination and allow everyone to build up Physics (or science) identities.…”
Section: Discussionmentioning
confidence: 99%
“…The Physics Olympiad presents a typically predominantly male science environment, while at the same time presenting a selective sample of participants who have shown ongoing interest in science by entering the competition and pursuing physics knowledge beyond school education. Although the competition does not explicitly broadcast stereotypes about women having lacking talent for science, previous research has indicated that stereotype threat has negative effects on female participants of science competitions (e.g., Steegh et al, 2019;Ladewig et al, 2020). It seems advisable to implement growth mindset and values affirmation interventions to protect female participants of the German Physics Olympiad from the potential damage by those stereotypes.…”
Section: The Present Studymentioning
confidence: 99%
“…These students show interest and intention to engage in the domain by pursuing science outside the mandatory school curriculum. Nonetheless, female students who participate in such extracurricular science activities experience stereotype threat (see Ladewig at al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Variables predicting students' decisions to participate in science competitions were found to range from social roles and personal values to prior experiences and self‐schemata (see Steegh et al, 2019 for a review). In more recent work specifically focusing on the representation and achievements of girls in science Olympiads, the negative role of gender‐science stereotypes was closely examined and linked to interest (Ladewig et al, 2020; Steegh, Höffler, Höft, & I., 2021a).…”
Section: Introductionmentioning
confidence: 99%